Victimization experienced by justice-involved youth: perceived influences on their trajectories - Gouin, Mariane (Understanding desistance from crime and social and community (re)integration, 2024)
The link between victimization and criminality has been the crux of many studies, but few reflect the perspectives and realities of justice-involved youth in Québec, Canada. This chapter will focus on a secondary qualitative analysis of some of the interviews that took place during a project under the (RE)SO 16-35 Partnership Research Program. These conversations shed light on the perceptions of participants who have been victims of one or several forms of abuse during childhood and/or adolescence in terms of how they perceive the impact of this abuse on their criminality in adulthood. The final sample of this study is composed of 23 participants, including 7 women and 16 men between the ages of 18 and 33. The findings show that several participants believe that their experiences of victimization led them to carry out criminal acts and that the use of psychoactive substances played an important role in this link. The findings will be discussed on the basis of different theories presented in the Introduction.